Pyrolysis of ground pine chip and ground pellet particles. (4th August 2016) - Rezaei, Hamid; Yazdanpanah, Fahimeh; Lim, C. Jim; Lau, Anthony; Sokhansanj, Shahab
Abstract: In addition to particle size, biomass density influences heat and mass transfer rates during the thermal treatment processes. In this research, thermal behaviour of ground pine chip particles and ground pine pellet particles in the range of 0.25–5 mm was investigated. A single particle from ground pellets was almost 3 to 4 times denser than a single particle from ground chips at a similar size and volume of particle. Temperature was ramped up from room temperature (∼25 °C) to 600 °C with heating rates of 10, 20, 30, and 50 °C/min. Pellet particles took 25–88 % longer time to dry than the chip particles. Microscopic examination of 3 mm and larger chip particles showed cracks during drying. No cracks were observed for pellet particles. The mass loss due to treatment at temperatures higher than 200 °C was about 80 % both for chip and pellet particles. It took 4 min for chip and pellet particles to lose roughly 63 % of their dry mass at a heating rate of 50 °C/min. The SEM structural analysis showed enlarged pores and cracks in cell walls of the pyrolyzed wood chips. These pores were not observed in pyrolyzed pellet particles.